Elucidating the role of TiCl4 post-treatment on percolation of TiO2 electron transport layer in perovskite solar cells. (1st July 2020) - Amalathas, Amalraj Peter; Landová, Lucie; Huminiuc, Teodor; Horák, Lukáš; Conrad, Brianna; Polcar, Tomas; Holovský, Jakub
Abstract: The ideal electron transport layer of a high performance perovskite solar cell should have good optical transparency, high electron mobility, and an energy level alignment well-matched with the perovskite material. In this work, we investigate the role of TiCl4 post-treatment of the mesoporous TiO2 electron transport layer by varying the concentration of TiCl4 and characterizing optical and electrical properties, charge carrier dynamics, and photovoltaic performance of mesoscopic CH3 NH3 PbI3 solar cells. It is found that the TiCl4 treatment provides an additional interconnection between the TiO2 particles, leading to better percolation as evident from high resolution cross-section images and chemical maps. This enhances effective electron mobility in the material as well as significantly reduces average sub-bandgap absorption due to defects and electronic disorder determined by photothermal deflection spectroscopy. Moreover, improvement of interfacial contact due to a smoother surface contributes to more efficient charge extraction and suppressed charge recombination and reduced hysteresis. As a result, the optimized device based on TiCl4 post-treated mesoporous TiO2 achieved the highest conversion efficiency of 17.4% compared with 14.1% for the device with pristine mesoporous TiO2 .